2019
DOI: 10.1002/osp4.336
|View full text |Cite
|
Sign up to set email alerts
|

Self‐report dieting and long‐term changes in body mass index and waist circumference

Abstract: Summary Objective This prospective study explores whether dieting attempts and previous changes in weight predict changes in body mass index (BMI) and waist circumference (WC). Methods The study was based on the representative Finnish Health 2000 Survey and on its follow‐up examination 11 years later. The sample included 2,785 participants, aged 30–69. BMI and WC were determined at health examinations. Information on dieting attempts and previous changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…During their nutritional rehabilitation after losing 25-29% of their body weight over 24 weeks of semistarvation, they showed fat overshooting of 4 kg on average but ranging between 0 and 9 kg, with those showing higher fat overshooting being the leanest, as evidenced from an inverse exponential relationship between the kg of fat overshot and initial (pre-starvation) body fat% [36]. Thus, a high dependency of postdieting fat overshooting upon the initial adiposity is a central tenet in explaining the findings of prospective studies showing a more consistent association between dieting to lose weight and increased risks for major weight gain in individuals initially of normal-weight than in people initially with overweight or obesity [6,11,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During their nutritional rehabilitation after losing 25-29% of their body weight over 24 weeks of semistarvation, they showed fat overshooting of 4 kg on average but ranging between 0 and 9 kg, with those showing higher fat overshooting being the leanest, as evidenced from an inverse exponential relationship between the kg of fat overshot and initial (pre-starvation) body fat% [36]. Thus, a high dependency of postdieting fat overshooting upon the initial adiposity is a central tenet in explaining the findings of prospective studies showing a more consistent association between dieting to lose weight and increased risks for major weight gain in individuals initially of normal-weight than in people initially with overweight or obesity [6,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to the increasing prevalence of overweight and obesity worldwide, the prevalence of dieting is also rising, and current estimates indicate that 40% of adults have tried to lose weight at some point during the last 5 years [1]. With studies of the long-term outcomes showing that at least onethird of dieters regain more weight than they lost [2], together with prospective studies indicating that dietingwhether in adults [3][4][5][6][7][8][9][10][11], adolescents [12][13][14][15][16] or children [17][18][19]-predicts future weight gain and obesity, there is concern as to whether dieting may paradoxically be promoting exactly the opposite of what it is intended to achieve [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individuals with IWL showed a statistically significant elevated risk of T2D occurrence, with an HR of 1.58 (95% CI 1. 23 Epidemiology/Health services research Epidemiology/Health services research Epidemiology/Health services research Epidemiology/Health services research statistically significantly increased risk in those with IWL could be seen in the subgroups of men, individuals with low or intermediate education, individuals with obesity, individuals with low PA, never-smokers, individuals with the lowest energy intake and individuals with short sleep.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of epidemiological follow-up studies have suggested that dieting predicts weight gain. [21][22][23] Some studies have indicated the association to be accentuated in individuals with normal weight. 22 23 It has been suggested that dieting attempts may act as a proxy for susceptibility to gain weight.…”
mentioning
confidence: 99%